The Aftermath of the Economic Crisis: Healthcare Systems' Inequalities in Europe - Silvia Palasca; Sebastian Enea (CES Working Papers, 2014)
During an economic downturn the non-productive sectors (education, health, and social services) are the most exposed to sudden policy changes, as a result of austerity measures. This article aims to assess the impact of the late 2000's crisis on some European countries' healthcare systems in order to highlight the link between the breakdown of the economic context and the negative outcomes on a social level. In this regard, a panel data analysis was employed, focusing on out-of-pocket health expenses as an estimation of a nation's wellbeing and healthcare development level. The cross-time results indicated a clear collapse of all national healthcare systems in 2009 while the cross-section effects implied that the twenty three countries could be divided in three groups according to their healthcare policy, especially regarding health insurance. Thus, countries should pay more attention to the private insurances component of the healthcare systems as the others are defenseless against business cycle fluctuations.
Keywords: C23; I13; I14; 330; economic crisis; healthcare; out-of-pocket payments; social inequalities; panel data